2014
DOI: 10.1016/j.exppara.2014.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Copper and selenium: Auxiliary measure to control infection by Haemonchus contortus in lambs

Abstract: The aim of this study was to evaluate the effects of selenium and copper on oxidative stress and its performance in lambs experimentally infected with Haemonchus contortus. Twenty-eight five-months old lambs were experimentally infected by the oral route with 5000 third-stage infective larvae and allocated into four groups, i.e., untreated animals, animals treated intramuscularly with sodium selenite (0.2 mg kg(-1)), animals treated subcutaneously with copper (3.5 mg kg(-1)), and animals treated with sodium se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
4
11
0
Order By: Relevance
“…The OSI values of Group IV were lower than those of Group III, demonstrating that zinc enhanced the antioxidant action of the organism. Similarly of study reported for Leal et al (2014) that reduction of lipid peroxidation in sheep infected by H. contortus and treated of copper and selenium.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…The OSI values of Group IV were lower than those of Group III, demonstrating that zinc enhanced the antioxidant action of the organism. Similarly of study reported for Leal et al (2014) that reduction of lipid peroxidation in sheep infected by H. contortus and treated of copper and selenium.…”
mentioning
confidence: 79%
“…Previous studies have demonstrated that selenium, with or without copper, can reduce the oxidative stress caused by H. contortus infection (Leal et al, 2014). However, until now, there are no reports that describe the effects of zinc edetate on sheep infected by H. contortus.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Our results also indicated that lambs in the control and Herbmix groups infected with H. contortus could have Se deficiency, which would decrease GPx activity relative to the Selplex group, thereby probably also increasing the vulnerability of cells to the harmful actions of reactive oxygen species [ 53 ]. Se can reduce the effects of oxidative stress caused by infection with H. contortus and can also reduce EPG and the number of adult parasites in association with another trace element, copper [ 14 ]. This activity of Se was apparent throughout our experiment on EPGs and the reduction in worm burdens after necropsy.…”
Section: Discussionmentioning
confidence: 99%
“…The production of reactive oxygen species by host phagocytes (macrophages, eosinophils, and neutrophils) plays an important role in the ability of hosts to expel GIN parasites [ 13 ]. These reactive oxygen species cause immunosuppression by intensive oxidative processes [ 14 ]. These processes, however, can be neutralized by an antioxidant defensive system represented by enzymes such as catalase, superoxide dismutase, glutathione peroxidase (GPx) and by nonenzymatic antioxidants such as vitamins A, C, and E [ 15 ].…”
Section: Introductionmentioning
confidence: 99%